2021
DOI: 10.1093/ons/opab274
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Cochlear Nerve Monitoring for Vestibular Schwannoma Resection and Simultaneous Cochlear Implantation in Neurofibromatosis Type 2: A Case Series

Abstract: BACKGROUND Neurofibromatosis type 2 (NF2) often results in profound hearing loss and cochlear implantation is an emerging hearing rehabilitation option. However, cochlear implant (CI) outcomes in this population vary, and intraoperative monitoring to predict cochlear nerve viability and subsequent outcomes is not well-established. OBJECTIVE To review the use of intraoperative electrically evoked cochlear nerve monitoring in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…If surgery is recommended, the decision of devices is more nuanced given the potential for nerve disruption. Using a commercial CI, one can measure both evoked auditory brainstem response and stapedial reflexes, which may provide an intraoperative assessment of cochlear nerve integrity (10,26,27). For patients implanted after surgery, transtympanic promontory stimulation testing may be an option for testing cochlear nerve integrity (28).…”
Section: Discussionmentioning
confidence: 99%
“…If surgery is recommended, the decision of devices is more nuanced given the potential for nerve disruption. Using a commercial CI, one can measure both evoked auditory brainstem response and stapedial reflexes, which may provide an intraoperative assessment of cochlear nerve integrity (10,26,27). For patients implanted after surgery, transtympanic promontory stimulation testing may be an option for testing cochlear nerve integrity (28).…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been suggested to best preserve the cochlear nerve during tumor resection for continued successful implant use. 26,27…”
Section: Discussionmentioning
confidence: 99%
“…If surgery is needed, some data suggest that the implant may be used for intraoperative auditory brainstem response and neural response imaging for cochlear nerve monitoring. This technique has been suggested to best preserve the cochlear nerve during tumor resection for continued successful implant use 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of conventional measures such as auditory-evoked auditory brainstem response (ABR) or cochlear nerve action potentials has limited utility in patients with poor baseline hearing and cannot be used to monitor cochlear nerve integrity with the translabyrinthine approach, where acoustic hearing is necessarily lost during labyrinthectomy. Recent studies have demonstrated the utility of electrically evoked auditory brainstem response (eABR) and streaming neural response telemetry (NRT) for intraoperative monitoring of the cochlear nerve with a commercial cochlear implant system or a test electrode and have shown increased accuracy in predicting CI performance after VS resection (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%